Stretched Film

JP7639644B2Active Publication Date: 2025-03-05OJI HLDG CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021163121
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-10-01
Publication Date
2025-03-05
Estimated Expiration
2041-10-01

AI Technical Summary

Benefits of technology

【0009】 本発明の延伸フィルムは、延伸性に優れ、透明性も高い。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639644000001
    Figure 0007639644000001
Patent Text Reader

Abstract

To provide a stretched film having excellent stretchability and also high transparency.SOLUTION: The stretched film of the present invention includes a layer a containing a crystalline polyolefin resin A, a crystalline biomass plastic B, and a thermoplastic elastomer C. The thermoplastic elastomer C has an MFR of 1-35 g / 10 min. An internal haze value measured according to JIS K7136 is 0.01-1% per 1 μm thickness. The stretched film of the present invention has excellent stretchability and also high transparency.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a stretched film. [Background technology]

[0002] Resin films are excellent in various properties such as moisture resistance, water resistance, and oil resistance, as well as good mechanical strength, and therefore are widely used in a variety of applications, such as packaging materials for foods and medicines, and protective films for displays, making them highly valuable functional materials.

[0003] On the other hand, in recent years, various problems have been raised, such as the increase in the amount of discarded plastic materials and concerns about global warming caused by carbon dioxide generated during the incineration of plastic materials. For this reason, biodegradable biomass plastics have attracted much attention from the perspective of consideration for the global environment and the human body, and the development of various materials that combine conventional plastic materials with biomass plastics has been actively pursued (for example, see Patent Documents 1 and 2, etc.). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2008 / 23758 [Patent Document 2] Special Publication No. 2017-519863 Summary of the Invention [Problem to be solved by the invention]

[0005] However, since thermoplastic resins, especially crystalline thermoplastic resins, and biomass plastics are materials that do not easily mix with each other, even when a film is formed by combining the two, they often do not mix uniformly with each other (are not compatible). Because of this, it is difficult to obtain a sufficiently stretched film, and there are various problems such as the transparency being easily impaired, so the uses of film materials obtained by blending crystalline thermoplastic resins and biomass plastics have been significantly limited.

[0006] The present invention has been made in view of the above, and an object of the present invention is to provide a stretched film that has excellent stretchability and high transparency. [Means for solving the problem]

[0007] As a result of intensive research into achieving the above-mentioned object, the inventors have found that the above-mentioned object can be achieved by using a specific thermoplastic elastomer C and adjusting the internal haze value within an appropriate range, and have thus completed the present invention.

[0008] That is, the present invention includes, for example, the subject matter described in the following sections. Item 1 The laminated sheet has a layer a containing a crystalline polyolefin resin A, a crystalline biomass plastic B, and a thermoplastic elastomer C, The MFR of the thermoplastic elastomer C is 1 to 35 g / 10 min; A stretched film having an internal haze value of 0.01 to 1% per 1 μm of thickness, measured in accordance with JIS K7136. Section 2 Item 2. The stretched film according to item 1, wherein the ratio of the diffuse transmittance at a diffusion angle of 3° to the diffuse transmittance at a diffusion angle of 0° is 20% or less. Section 3 The MFR of the crystalline polyolefin resin A is 1 to 4 g / 10 min, Item 3. The stretched film according to item 1 or 2, wherein the MFR of the crystalline biomass plastic B is 5 to 80 g / 10 min. Section 4 the layer a contains the crystalline polyolefin-based resin A in an amount of 30 to 96% by mass relative to the total mass of the crystalline polyolefin-based resin A, the crystalline biomass plastic B, and the thermoplastic elastomer C; The content of the crystalline biomass plastic B is 3 to 69 mass%. Item 4. The stretched film according to any one of items 1 to 3. Section 5 Item 5. The stretched film according to any one of items 1 to 4, wherein the crystalline polyolefin resin A has a melting point of 150° C. or higher. Section 6 Item 6. The stretched film according to any one of items 1 to 5, wherein the thermoplastic elastomer C is a styrene-based elastomer. Effect of the Invention

[0009] The stretched film of the present invention has excellent stretchability and high transparency. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, embodiments of the present invention will be described in detail. In this specification, the expressions "containing" and "comprise" include the concepts of "containing", "comprises", "consists essentially of" and "consists only of".

[0011] The stretched film of the present invention comprises a layer a containing a crystalline polyolefin resin A, a crystalline biomass plastic B, and a thermoplastic elastomer C, wherein the thermoplastic elastomer C has an MFR of 1 to 70 g / 10 min and an internal haze value measured in accordance with JIS K7136 of 0.01 to 1% per 1 μm of thickness.

[0012] The stretched film of the present invention has excellent stretchability and high transparency despite containing biomass plastic. Note that, just to be sure, the fact that the stretched film has excellent stretchability means that the material (raw sheet) for forming the stretched film is easy to stretch, so that the obtained stretched film can be in a sufficiently stretched state.

[0013] The stretched film of the present invention includes at least a layer a made of a resin. The layer a serves as a core layer in the stretched film. First, each component contained in the layer a will be described.

[0014] (Crystalline polyolefin resin A) The crystalline polyolefin resin A is not particularly limited as long as it is a polyolefin having crystallinity, and examples thereof include a wide variety of known crystalline polyolefin resins. The crystalline nature of a polyolefin resin can be determined by a differential scanning calorimeter. For example, in a differential scanning calorimeter for polyolefin resins (e.g., Perkin-Elmer's input compensation type DSC, Diamond DSC), the temperature is raised from -40°C to 300°C at a rate of 20°C / min under nitrogen flow, held at 300°C for 5 minutes, cooled to -40°C at 20°C / min, held at -40°C for 5 minutes, and then heated again to 300°C at 20°C / min. If a clear melting peak appears in the DSC curve obtained, the polyolefin resin can be determined to be crystalline. If such a clear melting peak does not appear, the polyolefin resin is non-crystalline.

[0015] An example of the crystalline polyolefin resin A is a polymer obtained by polymerizing an olefin. The olefin preferably has 2 to 20 carbon atoms, more preferably 2 to 10 carbon atoms, and even more preferably 3 to 6 carbon atoms.

[0016] Specific examples of the crystalline polyolefin resin A include crystalline polyethylene resin, polypropylene resin, poly(1-butene) resin, polyisobutene resin, poly(1-pentene) resin, and poly(4-methylpentene-1) resin. The crystalline polyolefin resin is preferably a crystalline polypropylene resin in that it is easily mixed (compatible) with the crystalline biomass plastic B. The crystalline polyolefin resin may be one type alone or a mixture of two or more types.

[0017] The crystalline polypropylene-based resin is more preferably at least one selected from the group consisting of propylene homopolymers and propylene and ethylene copolymers. When the crystalline polyolefin-based resin is a crystalline propylene homopolymer, compatibility with the crystalline biomass plastic B is likely to be improved, and the mechanical strength and heat resistance of the film are likely to be improved, while when the crystalline polyolefin-based resin is a crystalline propylene-ethylene copolymer, compatibility with the crystalline biomass plastic B is likely to be improved, and the fold crack resistance at low temperatures is improved, and the surface gloss is likely to be reduced.

[0018] When the crystalline polypropylene resin contains two components, the crystalline propylene homopolymer and the crystalline propylene-ethylene copolymer, a film having excellent heat resistance and low-temperature fold crack resistance is easily obtained. When the crystalline polypropylene resin contains both the crystalline propylene homopolymer and the crystalline propylene-ethylene copolymer, the preferred mass ratio is crystalline propylene homopolymer (P1):crystalline propylene-ethylene copolymer (P2)=70:30-99:1, more preferably P1:P2=75:25-98:2, and even more preferably P1:P2=78:22-97:3.

[0019] The crystalline propylene homopolymer is preferably a crystalline isotactic polypropylene resin. The crystalline isotactic polypropylene resin preferably has a mesopentad fraction ([mmmm]), which is a degree of stereoregularity determined by high-temperature nuclear magnetic resonance (NMR) measurement, of 92% to 98%, more preferably 93% to 97%. When the mesopentad fraction [mmmm] is 92% or more, the crystallinity of the resin is improved due to the high stereoregularity component, and high thermal stability and mechanical strength are easily obtained. On the other hand, when the mesopentad fraction [mmmm] is 98% or less, the stretchability is easily improved.

[0020] There are no particular limitations on the high-temperature NMR device that can be used to measure the mesopentad fraction ([mmmm]). For example, a commercially available high-temperature nuclear magnetic resonance (NMR) device capable of measuring the stereoregularity of polyolefins can be used. An example of this is the high-temperature Fourier transform nuclear magnetic resonance (high-temperature FT-NMR) JNM-ECP500 manufactured by JEOL Ltd. The observed nuclei are 13 The frequency is 125 C (125 MHz), the measurement temperature is 135°C, and the solvent used is ortho-dichlorobenzene (ODCB: a mixed solvent of ODCB and deuterated ODCB (volume ratio = 4 / 1)). The high-temperature NMR method can be performed by a known method, for example, the method described in "Japan Analytical Chemistry - Polymer Analysis Research Forum, ed., New Edition Polymer Analysis Handbook, Kinokuniya Shoten, 1995, p. 610". The measurement mode is single pulse proton broadband decoupling, pulse width 9.1 μsec (45° pulse), pulse interval 5.5 sec, number of accumulations 4500, and shift standard CH3 (mmmm) = 21.7 ppm.

[0021] The pentad fraction, which indicates the degree of stereoregularity, is calculated as a percentage from the integral intensity of each signal derived from a combination of five pentads (pentads) consisting of meso (m) pentads arranged in the same direction and racemo (r) pentads arranged in the opposite direction (mmmm, mrrm, etc.). For the assignment of each signal derived from mmmm, mrrm, etc., see, for example, the description of spectra in "T. Hayashi et al., Polymer, Vol. 29, p. 138 (1988)". The meso pentad fraction ([mmmm]) can be controlled by appropriately adjusting the polymerization conditions of the polypropylene resin, the type of catalyst, the amount of catalyst, and other polymerization conditions.

[0022] The melt mass flow rate (i.e., MFR) of the crystalline polyolefin resin A is not particularly limited. The MFR of the crystalline polyolefin resin A is preferably 1 to 4 g / 10 min, since the flowability is in a suitable range, the desired stretched film is easily produced, and the transparency is particularly high. The MFR of the crystalline polyolefin resin A in this specification refers to a value measured at 230°C and 21.18 N in accordance with JIS K-7210 (1999).

[0023] The melting point of the crystalline polyolefin resin A is not particularly limited. The melting point of the crystalline polyolefin resin A is preferably 150° C. or higher, in that the flowability is in a suitable range, making it easy to prepare a desired stretched film, and the transparency and heat resistance are particularly high. The melting point of the crystalline polyolefin resin A is preferably 170° C. or lower, in which case a stretched film excellent in stretchability and transparency is easily obtained.

[0024] The glass transition temperature of the crystalline polyolefin resin A is not particularly limited and can be, for example, 120° C. or lower. The crystalline polyolefin resin A may have a temperature of 50° C. or lower, or may be −30° C. to 30° C. The melting point and glass transition temperature of the crystalline polyolefin resin A are values ​​measured using a differential scanning calorimeter (for example, input compensation type DSC, Diamond DSC manufactured by Perkin-Elmer).

[0025] It is particularly preferable that the crystalline polyolefin resin A is the above-mentioned crystalline polypropylene resin, which has an MFR of 1 to 4 g / 10 min and a melting point of 150° C. or higher.

[0026] The crystalline polyolefin resin A can be produced, for example, by a known method, or can be obtained from a commercially available product. Representative commercially available products include, for example, homopolymers of the Prime Polypro (registered trademark) series manufactured by Prime Polymer Co., Ltd., PC412A manufactured by Sunallomer Co., Ltd., homopolymers of the Novatec (registered trademark) series manufactured by Japan Polypropylene Corporation, Daploy series manufactured by Borealis, 5014L series manufactured by Daehan Petrochemical Co., Ltd., homopolymers of the Sumitomo Noblen (registered trademark) series manufactured by Sumitomo Chemical Co., Ltd., and the like. In addition, commercially available products of crystalline propylene-ethylene copolymers include copolymers of the Prime Polypro (registered trademark) series manufactured by Prime Polymer Co., Ltd., copolymers of the Novatec PP (registered trademark) series and Wintech (registered trademark) series manufactured by Japan Polypropylene Corporation, and copolymers of the Sumitomo Noblen (registered trademark) series manufactured by Sumitomo Chemical Co., Ltd., and the like.

[0027] (Crystalline biomass plastic B) The crystalline biomass plastic B is not particularly limited as long as it is a resin having biodegradability, and may be, for example, a wide variety of known crystalline biomass plastics. The crystallinity of the biomass plastic can be determined by a differential scanning calorimeter, as with the crystalline polyolefin resin A.

[0028] Examples of the crystalline biomass plastic B include aliphatic polyester resins having biodegradability, such as polylactic acid, polyhydroxyalkanoic acid (excluding polylactic acid), polyhydroxybutyrate, polycaprolactone, polybutylene succinate, polybutylene succinate / adipate, polyethylene succinate, polymalic acid, polyglycolic acid, polydioxanone, and poly(2-oxetanone). The crystalline biomass plastic B may be a natural polymer, such as starch, cellulose, chitin, chitosan, gluten, gelatin, zein, soybean protein, collagen, and keratin. The crystalline biomass plastic B may be one type alone or a mixture of two or more types.

[0029] The crystalline biomass plastic B is preferably an aliphatic polyester resin, since it is easily mixed uniformly with the crystalline polyolefin resin A and a highly transparent stretched film can be easily obtained. Among these, it is more preferable that the crystalline biomass plastic B is one or more selected from the group consisting of polylactic acid, polyhydroxyalkanoic acid, and polymers of mixed monomers containing lactic acid and polyhydroxyalkanoic acid, and polylactic acid is particularly preferable.

[0030] As the polylactic acid, for example, a polylactic acid obtained by polycondensation of a lactic acid component as a raw material monomer, or other known polylactic acid can be widely used. The polylactic acid can contain only one of the optical isomers of L-lactic acid (L-form) and D-lactic acid (D-form), or both. As the polyhydroxyalkanoic acid, there can be mentioned a polymer of a hydroxycarboxylic acid component containing at least one of hydroxybutyric acid, hydroxyvaleric acid, hydroxypentanoic acid, hydroxycaproic acid, hydroxyheptanoic acid, glycolic acid, etc. As the polymer of a mixed monomer containing lactic acid and polyhydroxyalkanoic acid, there can be mentioned a polymer obtained by polycondensation of a lactic acid monomer and the hydroxycarboxylic acid component.

[0031] The melt mass flow rate of the crystalline biomass plastic B is not particularly limited. The MFR of the crystalline biomass plastic B is preferably 5 to 80 g / 10 min, since the fluidity is in a moderate range, the desired stretched film is easily produced, and the transparency is particularly high. The MFR of the crystalline biomass plastic B is preferably 7 g / 10 min or more, more preferably 10 g / 10 min or more, even more preferably 13 g / 10 min or more, particularly preferably 15 g / 10 min or more, and is preferably 50 g / 10 min or less, more preferably 40 g / 10 min or less, even more preferably 30 g / 10 min or less, and particularly preferably 25 g / 10 min or less. The MFR of the crystalline biomass plastic B in this specification refers to a value measured at 230 ° C. and 21.18 N in accordance with JIS K-7210 (1999).

[0032] There are no particular limitations on the melting point of the crystalline biomass plastic B. In terms of achieving a suitable range of fluidity to facilitate preparation of a desired stretched film and particularly high transparency and heat resistance, the melting point of the crystalline biomass plastic B is preferably 110°C or higher, more preferably 120°C or higher, even more preferably 130°C or higher, and particularly preferably 140°C or higher, and is preferably 200°C or lower, more preferably 190°C or lower, even more preferably 180°C or lower, and particularly preferably 170°C or lower.

[0033] The glass transition temperature of the crystalline biomass plastic B is not particularly limited and can be, for example, −40° C. to 70° C., more preferably 0° C. to 70° C. The melting point and glass transition temperature of the crystalline biomass plastic B are values ​​measured using a differential scanning calorimeter (for example, Perkin-Elmer's power compensation DSC, Diamond DSC).

[0034] The method for producing the crystalline biomass plastic B is not particularly limited, and for example, a method for producing a known biomass plastic can be widely adopted. The crystalline biomass plastic B can also be obtained from commercial products. Representative commercial products of polylactic acid include "4032D" (melting point 163°C) manufactured by NatureWorks, "L175" (melting point 175°C), "LX175" (melting point 155°C), and "LX930" (melting point 130°C) manufactured by Total Corbion. Other representative commercial products of the crystalline biomass plastic B include polyhydroxyalkanoate "ENMAT (registered trademark) Y1000P" manufactured by Tianan Biologic Material, polybutylene succinate "BioPBS (registered trademark) FZ91" and "BioPBS (registered trademark) FD82" manufactured by Mitsubishi Chemical Corporation, and polybutylene adipate terephthalate "Ecoflex (registered trademark)" manufactured by BASF Ltd.

[0035] (Thermoplastic elastomer C) Thermoplastic elastomer C has a melt mass flow rate (MFR) of 1 to 70 g / 10 min, and is a component that can act as a compatibilizer to enhance the compatibility of crystalline polyolefin resin A and crystalline biomass plastic B. By including thermoplastic elastomer C, the compatibility of crystalline polyolefin resin A and crystalline biomass plastic B is enhanced, and internal haze can be significantly reduced, the transparency of the stretched film is further improved, and the strength (for example, puncture strength described below) is excellent. The MFR of thermoplastic elastomer C in this specification refers to a value measured at 230°C and 21.18 N in accordance with JIS K-7210 (1999).

[0036] If the MFR of the thermoplastic elastomer C is less than 1 g / 10 min, the effect of increasing the compatibility between the crystalline polyolefin resin A and the crystalline biomass plastic B cannot be obtained, and the transparency of the stretched film deteriorates. If the MFR of the thermoplastic elastomer C exceeds 70 g / 10 min, the effect of increasing the compatibility between the crystalline polyolefin resin A and the crystalline biomass plastic B cannot be obtained, and the transparency of the stretched film deteriorates, causing a decrease in film strength.

[0037] The MFR of the thermoplastic elastomer C is preferably 1.5 g / 10 min or more, more preferably 2 g / 10 min or more, even more preferably 2.5 g / 10 min or more, and particularly preferably 3 g / 10 min or more. The MFR of the thermoplastic elastomer C is preferably 50 g / 10 min or less, more preferably 40 g / 10 min or less, even more preferably 35 g / 10 min or less, and particularly preferably 30 g / 10 min or less.

[0038] The type of the thermoplastic elastomer C is not particularly limited as long as the MFR is 1 to 70 g / 10 min, and may be a wide variety of known thermoplastic elastomers. Among them, the thermoplastic elastomer C is preferably a styrene-based elastomer. The styrene-based elastomer is an elastomer that contains at least a styrene unit or a styrene derivative unit.

[0039] The styrene-based elastomer may contain, in addition to the styrene unit, at least one other unit selected from the group consisting of an olefin unit, a (meth)acrylic acid unit, a (meth)acrylic acid ester unit, and a (meth)acrylonitrile unit. The olefin unit, the (meth)acrylic acid unit, the (meth)acrylic acid ester unit, and the (meth)acrylonitrile unit may each be one type alone or two or more types.

[0040] Specific examples of the styrene-based elastomer include a styrene-ethylene-butylene-styrene block copolymer, a styrene-grafted ethylene-glycidyl methacrylate copolymer, and a styrene-ethylene-propylene-styrene copolymer. Of these, the styrene-based elastomer is preferably a styrene-ethylene-butylene-styrene block copolymer.

[0041] In the styrene-based elastomer, the content of the styrene unit or the styrene derivative unit is not particularly limited. For example, the content of the styrene unit or the styrene derivative unit in the styrene-based elastomer is preferably 10 to 80% by mass. In this case, the stretchability of the stretched film is excellent and the internal haze is particularly small, so that the transparency is high and the strength is particularly excellent. The content of the styrene unit or the styrene derivative unit in the styrene-based elastomer is more preferably 20% by mass or more, and even more preferably 30% by mass or more. In addition, the content of the styrene unit or the styrene derivative unit in the styrene-based elastomer is more preferably 70% by mass or less, and even more preferably 60% by mass or less.

[0042] The thermoplastic elastomer C can have a structure such as a block copolymer, a random copolymer, or a graft copolymer.

[0043] The glass transition temperature of the thermoplastic elastomer C is not particularly limited and can be, for example, −60 to −10° C. The glass transition temperature of the thermoplastic elastomer C is a value measured using a differential scanning calorimeter (for example, a power compensation type DSC, Diamond DSC manufactured by Perkin-Elmer).

[0044] The thermoplastic elastomer C can be obtained, for example, by a known production method, or can be obtained from a commercial product, etc. Representative commercial products of the thermoplastic elastomer C include, for example, JSR ethylene-ethylene-butylene-styrene block copolymer "DYNARON (registered trademark)", hydrogenated SBR "DYNARON (registered trademark)" manufactured by JSR Corporation, styrene-ethylene-propylene-styrene copolymer "SEPTON 2002 (registered trademark)" manufactured by Kuraray Co., Ltd., and others such as "TUFTECH (registered trademark)" manufactured by Asahi Kasei Corporation, "MODIPER A1100 (registered trademark)", "MODIPER A1401 (registered trademark)", "MODIPER A3400 (registered trademark)", "MODIPER A4100 (registered trademark)", and "MODIPER A5400 (registered trademark)" manufactured by NOF Corporation.

[0045] (layer a) The layer a functions as a core layer of the stretched film and is formed of resin components including a crystalline polyolefin resin A, a crystalline biomass plastic B and a thermoplastic elastomer C.

[0046] In the layer a, the content ratio of the crystalline polyolefin resin A relative to the total mass of the crystalline polyolefin resin A, the crystalline biomass plastic B, and the thermoplastic elastomer C is not particularly limited.

[0047] For example, in terms of providing a good stretchability of the stretched film, facilitating adjustment of the internal haze to a desired range, and facilitating improvement of strength, it is preferable that layer a contains 30 to 96 mass% of the crystalline polyolefin resin A and 3 to 69 mass% of the crystalline biomass plastic B relative to the total mass of the crystalline polyolefin resin A, the crystalline biomass plastic B, and the thermoplastic elastomer C. In this case, the remainder is thermoplastic elastomer C (i.e., the content of thermoplastic elastomer C is 1 to 10 mass%).

[0048] Layer a preferably contains 40% by mass or more of the crystalline polyolefin resin A, more preferably 50% by mass or more, and more preferably 90% by mass or less, and even more preferably 85% by mass or less of the crystalline polyolefin resin A relative to the total mass of the crystalline polyolefin resin A, the crystalline biomass plastic B, and the thermoplastic elastomer C.

[0049] Layer a preferably contains 10% by mass or more of the crystalline biomass plastic B, and even more preferably 15% by mass or more of the crystalline biomass plastic B, relative to the total mass of the crystalline polyolefin resin A, the crystalline biomass plastic B, and the thermoplastic elastomer C, and more preferably contains 55% by mass or less, and even more preferably contains 45% by mass or less of the crystalline biomass plastic B.

[0050] Layer a preferably contains 1.5% by mass or more of the thermoplastic elastomer C, and more preferably 2% by mass or more, and more preferably 8% by mass or less, and even more preferably 7% by mass or less, based on the total mass of the crystalline polyolefin resin A, the crystalline biomass plastic B, and the thermoplastic elastomer C.

[0051] In a particularly preferred configuration of the layer a, the crystalline polyolefin resin A is a crystalline polypropylene resin, the crystalline biomass plastic B is polylactic acid, and the thermoplastic elastomer C is a styrene elastomer.

[0052] The resin components constituting layer a may consist only of the crystalline polyolefin resin A, the crystalline biomass plastic B, and the thermoplastic elastomer C. However, this does not exclude components that are inevitably contained in this case. Furthermore, as long as the effects of the present invention are not impaired, layer a may contain other resins in addition to the crystalline polyolefin resin A, the crystalline biomass plastic B, and the thermoplastic elastomer C. Examples of other resins include various resins contained in known stretched films.

[0053] The content of the other resin is preferably 10% by mass or less, and more preferably 1% by mass or less, based on the total mass of the resin components contained in the layer a.

[0054] (Stretched film) The stretched film of the present invention includes at least the layer a, and has an internal haze value of 0.01 to 1% per 1 μm of thickness measured according to JIS K7136. If the internal haze value per 1 μm of the stretched film is less than 0.01%, the film needs to be extremely thin, which causes a problem that the film cannot withstand practical strength. If the internal haze value per 1 μm of the stretched film is more than 1%, the transparency is deteriorated.

[0055] The internal haze value per 1 μm of the stretched film thickness is preferably 0.03% or more, more preferably 0.04% or more, even more preferably 0.05% or more, and particularly preferably 0.06% or more. The internal haze value per 1 μm of the stretched film thickness is preferably 0.7% or less, more preferably 0.6% or less, even more preferably 0.5% or less, and particularly preferably 0.4% or less.

[0056] The internal haze value of a stretched film is a value measured in accordance with JIS-K7136 using a haze meter NDH-5000 manufactured by Nippon Denshoku Industries Co., Ltd. Specifically, the internal haze of a stretched film is measured using a haze meter, and the measured value is divided by the thickness of the stretched film to obtain the "internal haze value of the film per 1 μm thickness (% / μm)."

[0057] The internal haze refers to the haze of a stretched film that is obtained by excluding the haze caused by the scattering factors on the film surface from the light scattering factors in the haze of the stretched film and taking into account only the scattering factors inside the stretched film. In other words, the internal haze does not include the influence of the unevenness of the film surface, for example.

[0058] In the stretched film of the present invention, the ratio of the diffuse transmittance at a diffusion angle of 3° to the diffuse transmittance at a diffusion angle of 0° is preferably 20% or less. In other words, in measuring the diffuse transmittance of the stretched film of the present invention, when the diffuse transmittance at a diffusion angle of 0° is defined as D(0) and the diffuse transmittance at a diffusion angle of 3° is defined as D(3), the following formula is satisfied: {D(3) / D(0)}×100 is preferably 20% or less. In this case, the transparency of the stretched film becomes significantly excellent, and the clarity of the transmitted image tends to be good.

[0059] In the stretched film of the present invention, the ratio of the diffuse transmittance at a diffusion angle of 3° to the diffuse transmittance at a diffusion angle of 0° is more preferably 19% or less, and even more preferably 18% or less. The ratio of the diffuse transmittance at a diffusion angle of 3° to the diffuse transmittance at a diffusion angle of 0° may be, for example, 0 or may be 0.1% or more.

[0060] The stretched film of the present invention is preferably transparent or translucent, and is preferably transparent, that is, a transparent stretched film.

[0061] The stretched film of the present invention has a layer a composed of a predetermined resin component, and therefore has excellent strength. For example, the stretched film of the present invention can have a puncture strength of 2.5N or more and 8N or less. This makes the stretched film excellent in strength, and is suitable for various packaging applications, for example. The puncture strength of the stretched film of the present invention is preferably 3N or more, more preferably 3.5N or more, and even more preferably 4N or more.

[0062] The stretched film of the present invention may have a single-layer structure including only layer a (i.e., a core layer), or may have a so-called laminate structure including layers other than layer a. When the stretched film has a laminate structure, for example, a laminate obtained by laminating other layers to one or both sides of layer a can be mentioned. Examples of the other layers include resin layers other than layer a, and specifically, resin layers having a heat seal function (heat seal layer) and the like can be mentioned. For example, resin layers having a known heat seal function can be widely applied as the heat seal layer. Examples of layers other than the heat seal layer include layers having one or more functions such as antifogging properties, antistatic properties, adhesion, smoothness, glossiness, printability, blocking resistance, slipperiness, strength imparting properties, gas barrier properties against oxygen gas, ethylene gas, etc., water vapor barrier properties, odor component barrier properties, prevention of component migration of packaged contents, antibacterial properties, and antifungal properties.

[0063] When the stretched film of the present invention includes a layer other than the layer a, the other layer may be laminated by being directly bonded to the layer a, or another layer may be interposed between the layer a and the layer a. The other layer may be laminated on both sides or one side of the layer a.

[0064] The stretched film of the present invention may contain additives as optional components, if necessary. Examples of the additives include a wide variety of known additives that are applied to stretched films, such as heat stabilizers, antioxidants, organic and inorganic lubricants, chlorine scavengers, and antistatic agents.

[0065] The thickness of the stretched film of the present invention is not particularly limited and can be appropriately set depending on the intended use. The thickness of the stretched film is, for example, preferably 10 to 150 μm, more preferably 15 to 100 μm, and further preferably 20 to 60 μm.

[0066] As described above, the stretched film of the present invention has excellent transparency and is therefore suitable for use in packaging, food packaging, pharmaceutical packaging, decoration (including fashion), labels, tape substrates, printing substrates, stationery, home appliances, poster paper, thermal paper substrates, recording paper substrates, interior and exterior use of homes, automobiles, and the like.

[0067] (Method of manufacturing stretched film) The method for producing the stretched film of the present invention is not particularly limited, and for example, known production methods can be widely adopted. For example, the stretched film of the present invention can be produced by extruding a resin raw material containing at least the crystalline polyolefin resin A, the crystalline biomass plastic B, and the thermoplastic elastomer C to obtain a resin sheet, and stretching the resin sheet. Such a production method is abbreviated as "production method A".

[0068] The resin raw material can be prepared in the same manner as known preparation methods, for example, by dry blending resin pellets, powder, etc. using a batch mixer such as a tumbler or mixer, or a continuous metering mixer; or by supplying resin pellets, powder, etc., together with other resin pellets, powder, and / or additives as necessary, to a kneader and melt-kneading to obtain a melt blend resin composition; etc. Among these, it is preferable to prepare the resin raw material by melt kneading, in which case the crystalline polyolefin resin A and the crystalline biomass plastic B are easily mixed uniformly, and a stretched film having the desired haze is easily obtained.

[0069] As the kneader used for melt kneading, a known kneader can be used, and a single screw type, a twin screw type, or a multi-screw type having more than two screws can be used, and further, in the case of a screw type having two or more screws, either a co-rotating or counter-rotating kneading type can be used. A co-rotating twin screw type kneader is preferred because the crystalline thermoplastic resin A and the crystalline thermoplastic resin B are easily mixed uniformly.

[0070] The kneading temperature of the melt kneading is preferably in the range of 200°C to 300°C, more preferably 220°C to 280°C. By setting the temperature in the above range, the crystalline thermoplastic resin A and the crystalline thermoplastic resin B can be mixed more uniformly. In order to prevent deterioration of the resin during melt kneading, an inert gas such as nitrogen can be purged. The melt-kneaded resin can be pelletized to an appropriate size using a commonly known granulator to obtain melt blend resin composition pellets.

[0071] In the manufacturing method A, a resin sheet can be obtained using the resin raw material obtained as described above. Specifically, the resin raw material is fed to an extruder, heated and melted, and, if necessary, fine foreign matter and the like is removed using a filter or the like, and then the melt is extruded into a sheet shape from a T-die, thereby obtaining a resin sheet.

[0072] The extruder used to obtain the resin sheet can be, for example, a wide variety of known extruders. There is no limitation on the screw type of the extruder, and a single screw type, a twin screw type, or a multi-screw type having more than one screw may be used. When the resin raw material is prepared by the dry blending, the use of a twin screw type or a multi-screw type having more than one screw tends to provide excellent mixing and dispersibility. The extrusion temperature is preferably in the range of 200°C to 300°C, more preferably 220°C to 280°C. In order to prevent thermal deterioration of the resin during extrusion, an inert gas such as nitrogen can be purged.

[0073] The melt-extruded resin sheet is molded into a sheet shape by a known method, for example, by adhering the sheet to at least one metal drum set at a temperature of 25 to 120° C. using an air knife or other rolls, or by static electricity, and the resin sheet is obtained as a so-called raw sheet. The temperature of the metal drum is more preferably 30 to 80° C.

[0074] The manufacturing method A may further include, for example, a lamination step, which allows a resin sheet having a laminated structure to be obtained. For example, the manufacturing method A may include a lamination step when it is intended to obtain a stretched film in which another layer, such as a heat seal layer, is formed on one or both sides of the layer a.

[0075] In the lamination step, for example, a wide variety of lamination methods that have been conventionally employed can be used, and examples thereof include films obtained by laminating using a coextrusion method, a lamination method, a heat sealing method, etc.

[0076] In the manufacturing method A, the resin sheet (raw sheet) having the above-mentioned single layer or laminate structure is stretched. As the stretching method, known methods such as stretching between rolls with a peripheral speed difference, a tenter method, a tubular method, etc. can be used. As the stretching direction, uniaxial stretching, biaxial stretching, biaxial stretching in an oblique direction, etc. are possible, and in the case of stretching in two or more axes, both sequential stretching and simultaneous stretching are applicable. Among these, the simultaneous biaxial stretching method by the tenter method, the sequential biaxial stretching method by the tenter method, and the sequential biaxial stretching method in which the longitudinal (flow, MD) stretching is performed between rolls with a peripheral speed difference and then the transverse (width, TD) stretching is performed by the tenter method are preferred from the viewpoint of easiness of obtaining the desired stretched film. Hereinafter, a method of obtaining the stretched film of the present invention by the sequential biaxial stretching method will be described, but it is not limited thereto.

[0077] In the sequential biaxial stretching method, it is preferable to adjust the stretching temperature and stretch ratio according to the melting point and glass transition temperature of the resin used. First, the resin sheet (raw sheet) is kept at a temperature of preferably 100 to 180°C, more preferably 120 to 170°C, and stretched in the longitudinal direction preferably 2 to 10 times, more preferably 2.5 to 8 times, and even more preferably 3 to 6 times by passing it between rolls with a difference in peripheral speed or by a tenter method. Subsequently, the stretched film is stretched in the transverse direction preferably 2 to 12 times, more preferably 2.5 to 11.5 times, and even more preferably 3 to 11 times by a tenter method at a temperature of preferably 100 to 180°C, more preferably 120 to 175°C, and then relaxed, heat-set, and wound up.

[0078] The wound film can be cut to a desired product width after being subjected to an aging treatment preferably in an atmosphere of about 20 to 45° C. In this way, a stretched film excellent in stretchability, transparency, mechanical strength, etc. can be obtained. EXAMPLES

[0079] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the embodiments of these examples. In addition, unless otherwise specified, "parts" and "%" respectively indicate "parts by mass" and "% by mass".

[0080] The resins used in the examples and comparative examples are as follows. (Crystalline polyolefin resin (Component A)) Resin A-1: ​​Prime Polypro (registered trademark) E-200GP (manufactured by Prime Polymer Co., Ltd., melting point 161°C, MFR 2g / 10 min, Tg 112°C) Resin A-2: Wintec (registered trademark) WMX03 polymer (Japan Polypropylene Corporation, melting point 142°C, MFR 25g / 10min)

[0081] (Crystalline biomass plastic (Component B)) Resin B-1: Luminy (registered trademark) L175 (Total Corbion PLA, polylactic acid, MFR 19g / 10min) Resin B-2: Luminy (registered trademark) LX175 (Total Corbion PLA, polylactic acid, MFR 20g / 10min) Resin B-3: Luminy (registered trademark) LX930 (Total Corbion PLA, polylactic acid, MFR 21g / 10min) Resin B-4: BioPBS (registered trademark) FZ91 (manufactured by Mitsubishi Chemical Corporation, polybutylene succinate, MFR 16g / 10min) Resin B-5: Ecoflex (registered trademark) (manufactured by BASF Ltd., polybutylene adipate terephthalate, MFR 13g / 10min) Resin B-6: ENMAT (registered trademark) Y1000P (manufactured by Tianan Biologic Material Co., Ltd., polyhydroxyalkanoate, MFR 120g / 10min)

[0082] (Thermoplastic elastomer (Component C)) Resin C-1: DYNARON 9901P (JSR Corporation, styrene-ethylene-butylene-styrene block copolymer (styrene 53%), MFR 3.3g / 10min) Resin C-2: DYNARON 8600P (JSR Corporation, styrene-ethylene-butylene-styrene block copolymer (styrene 15%), MFR 30g / 10min) Resin C-3: Modiper A4100 (NOF Corporation, styrene grafted ethylene-glycidyl methacrylate copolymer (styrene 30%), MFR 1.2g / 10min) Resin C-4: Septon 2002 (Kuraray Co., Ltd., styrene-ethylene-propylene-styrene copolymer (styrene 30%), MFR 70g / 10min) Resin C-5: AR-SC-0 (Toagosei, styrene-based elastomer)

[0083] [Resin melting point, glass transition temperature] The melting point and glass transition temperature of the resins used in the examples and comparative examples were calculated using a Perkin-Elmer input compensation type DSC, Diamond DSC, according to the following procedure. 5 mg of each resin was weighed out, packed into an aluminum sample holder, and set in a DSC device. Under nitrogen flow, the temperature was raised from -40°C to 300°C at a rate of 20°C / min, held at 300°C for 5 minutes, cooled to -40°C at 20°C / min, and held at -40°C for 5 minutes. The melting point and glass transition temperature were obtained from the DSC curve when the temperature was raised again to 300°C at 20°C / min. The melting peak (the maximum melting peak when multiple melting peaks are shown) defined in 9.1(1) of JIS-K7121 was taken as the melting point, and the midpoint glass transition temperature defined in 9.3(1) of JIS-K7121 was taken as the glass transition temperature.

[0084] [Internal haze of film] The internal haze of the stretched film was measured in accordance with JIS K7136 using a haze meter NDH-5000 manufactured by Nippon Denshoku Industries Co., Ltd. Specifically, the front and back surfaces of the stretched film were filled with liquid paraffin (manufactured by Wako Pure Chemical Industries, for infrared analysis) to wet the measurement area, and the internal haze was measured. The measured value was divided by the thickness of the stretched film to obtain the internal haze value of the film per 1 μm thickness (% / μm).

[0085] [Stretchability] The stretchability was evaluated using a Bruckner batch-type biaxial stretching machine KARO. The stretching method employed was a sequential biaxial stretching method in which the film was stretched in the longitudinal direction and then in the transverse direction. The raw sheet was preheated in an oven set at a temperature of 150°C, and after the film temperature (Ts) reached 135°C, it was stretched in the longitudinal direction at a stretching speed of 6 times / second to a stretching ratio of 5 times. Next, after the film temperature (Ts) reached 145°C in the same oven, it was stretched in the transverse direction at a stretching speed of 1 time / second to a stretching ratio of 10 times. The stretchability of the obtained stretched film was evaluated according to the following criteria. <Criteria for determining stretchability> ◯: The stretched film was uniformly stretched and the thickness variation was small. ×: The film was broken without being stretched.

[0086] [Diffuse transmittance ratio] The diffuse transmittance of the stretched films obtained in each Example and Comparative Example at diffusion angles of 0° and 3° was calculated, and when the diffuse transmittance at a diffusion angle of 0° was defined as D(0) and the diffuse transmittance at a diffusion angle of 3° was defined as D(3), the value of {D(3) / D(0)}×100 was calculated and used as the diffuse transmittance ratio (i.e., the ratio of the diffuse transmittance at a diffusion angle of 3° to the diffuse transmittance at a diffusion angle of 0°). The diffuse transmittance was measured using a variable angle goniophotometer (manufactured by Genesia Co., Ltd.).

[0087] [Piercing strength] The measurement was performed as follows according to the provisions of JIS Z 1707. A sample was fixed to a cylindrical jig, and a semicircular needle with a diameter of 1.0 mm and a tip radius of 0.5 mm was pierced into the surface of the sample (stretched film) at a speed of 50 mm / min, and the maximum load until the needle penetrated was measured.

[0088] Example 1 As shown in Table 1 below, the resin A-1 pellets as component A, the resin B-1 pellets as component B, and the resin C-1 pellets as component C were mixed in a mass ratio of 65:30:5 and dry-blended in a mixer to prepare a resin raw material. This resin raw material was fed from a hopper into a device in which a twin-screw extruder (L / D=25) equipped with a strand die was connected to a Labo Plastomill (registered trademark) (Model 4C150) manufactured by Toyo Seiki Seisakusho Co., Ltd., was connected, and melt-kneaded at 230°C. The melt-kneaded resin raw material was extruded into a strand shape, cooled with water, and cut into pellets with a strand cutter to obtain melt blend resin composition pellets. The pellets were fed from a hopper into a single-screw type extruder a, melted, and extruded from a single layer die. The extruded resin layer was cooled and solidified while being pressed by air pressure using an air knife onto a cooling drum controlled at 45°C to obtain a raw sheet.

[0089] The obtained raw sheet was stretched using a Bruckner batch biaxial stretching machine KARO. The stretching method was a sequential biaxial stretching method in which the film was stretched in the longitudinal direction and then in the transverse direction. The film was preheated in an oven with a set temperature of 150°C until the film temperature (Ts) reached 135°C, and then stretched to 5 times in the longitudinal direction at a stretching speed of 6 times / second. Next, the film was preheated in an oven with a set temperature of 165°C until the film temperature reached 145°C, and stretched to 10 times in the transverse direction at a stretching speed of 1 time / second. Next, in the same oven, the film was relaxed to 9.5 times in the transverse direction at a relaxation speed of 0.5 times / second, and then heat-set for 10 seconds, and then removed from the oven and cooled to room temperature to obtain a stretched film with a thickness of 25 μm.

[0090] (Examples 2 to 8, Comparative Examples 1 to 3) A stretched film having a thickness of 25 μm was obtained in the same manner as in Example 1, except that the resin raw material was prepared by setting the A component resin, B component resin, C component resin, and their compounding ratios (compounding ratios) as shown in Table 1 below. However, in Comparative Example 1, a stretched film could not be obtained because the film could not be stretched and broke.

[0091] [Table 1]

[0092] The preparation conditions and evaluation results of the stretched films obtained in each Example and Comparative Example are shown in Table 1. The stretched films obtained in the Examples had excellent stretchability, small internal haze values, excellent transparency, and high puncture strength.

Claims

1. The laminated plastic has a layer a containing a crystalline polyolefin resin A, a crystalline biomass plastic B, and a thermoplastic elastomer C, The MFR of the crystalline polyolefin resin A is 1 to 4 g / 10 min. The MFR of the crystalline biomass plastic B is 5 to 80 g / 10 min, The MFR of the thermoplastic elastomer C is 1 to 70 g / 10 min, A stretched film having an internal haze value of 0.01 to 1% per 1 μm of thickness, as measured in accordance with JIS K7136.

2. 2. The stretched film according to claim 1, wherein the ratio of the diffuse transmittance at a diffusion angle of 3° to the diffuse transmittance at a diffusion angle of 0° is 20% or less.

3. The layer a contains 30 to 96% by mass of the crystalline polyolefin-based resin A relative to the total mass of the crystalline polyolefin-based resin A, the crystalline biomass plastic B, and the thermoplastic elastomer C, The content ratio of the crystalline biomass plastic B is 3 to 69% by mass, The stretched film according to claim 1 or 2.

4. The stretched film according to any one of claims 1 to 3, wherein the melting point of the crystalline polyolefin resin A is 150°C or higher.

5. The stretched film according to any one of claims 1 to 4, wherein the thermoplastic elastomer C is a styrene-based elastomer.

Citation Information

Patent Citations

  • Film, molded article using the film, stretched film, heat shrinkable film, heat shrinkable label, and container with the label attached

    JP2009013405A

  • Oriented film and application thereof

    JP2011116929A

  • Polymeric blends and articles made therefrom

    JP2017519863A

  • Thermoplastic resin composition and molded article obtained from the same

    WO2008023758A1